Exploring the impact of the Baby-Friendly Hospital Initiative on trends in exclusive breastfeeding - Labbok Miriam H; Abrahams Sheryl W (BMC, 2009)
Abstract Background The Baby-Friendly Hospital Initiative (BFHI) seeks to support breastfeeding initiation in maternity services. This study uses country-level data to examine the relationship between BFHI programming and trends in exclusive breastfeeding (EBF) in 14 developing countries. Methods Demographic and Health Surveys and UNICEF BFHI Reports provided EBF and BFHI data. Because country programs were initiated in different years, data points were realigned to the year that the first Baby-Friendly hospital was certified in that country. Pre-and post-implementation time periods were analyzed using fixed effects models to account for grouping of data by country, and compared to assess differences in trends. Results Statistically significant upward trends in EBF under two months and under six months, as assessed by whether fitted trends had slopes significantly different from 0, were observed only during the period following BFHI implementation, and not before. BFHI implementation was associated with average annual increases of 1.54 percentage points in the rate of EBF of infants under two months (p < 0.001) and 1.11-percentage points in the rate of EBF of infants under six months (p < 0.001); however, these rates were not statistically different from pre-BFHI trends. Conclusion BFHI implementation was associated with a statistically significant annual increase in rates of EBF in the countries under study; however, small sample sizes may have contributed to the fact that results do not demonstrate a significant difference from pre-BFHI trends. Further research is needed to consider trends according to the percentages of Baby-Friendly facilities, percent of all births occurring in these facilities, and continued compliance with the program.